Chemopreventive Potential of Cereal Polyphenols. (18th August 2018) - Rao, Shiwangni; Santhakumar, Abishek B.; Chinkwo, Kenneth A.; Vanniasinkam, Thiru; Luo, Jixun; Blanchard, Christopher L.
Abstract: It has been identified that diet is one of the major contributing factors associated with the development of cancer and other chronic pathologies. In the recent years, supplementing regular diet with food and/or its components that contain chemopreventive properties has been considered an effective approach in reducing the incidence of cancer and other lifestyle associated diseases. This systematic review provides an exhaustive summary of the chemopreventive properties exhibited by everyday dietary ingredients such as rice, barley, oats, and sorghum. The studies both in vitro and in vivo reviewed have highlighted the potential role of their polyphenolic content as chemopreventive agents. Polyphenolic compounds including anthocyanins, tricin, protocatechualdehyde, avenanthramide, and 3-deoxyanthocyanins found in rice, barley, oats, and sorghum, respectively, were identified as compounds with potent bioactivity. Studies demonstrated that cereal polyphenols are likely to have chemopreventive activities, particularly those found in pigmented varieties. In conclusion, findings suggest that the consumption of pigmented cereals could potentially have an important role as a natural complementary cancer preventive therapeutic. However, further studies to develop a complete understanding of the mechanisms by which phenolic compounds inhibit cancerous cell proliferation are warranted.